1941
DOI: 10.1177/004051754101100302
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Silk Fibroin with Acid and with Base

Abstract: Silk contains a number of acidic and basic groups. The state of combination and the behavior of these groups are important in influencing the tensile and elastic properties of the fibroin and the adsorption of moisture and dyes.As part of a broad research program of the Textile Foundation Research Associateship at the National Bureau of Standards on the acidic and basic properties of fibers, this investigation was undertaken to determine the relationship between the quantities of hydroclaloric acid and potassi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1941
1941
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…It is seen that the stability of the silk to light increases WIth increase in pH of the solutions used for treatment of the silk. This is to be expected, since as shown by the titration curve of silk [6], the binding of cations also increases with increasing pH. In addition to pH, the chemical nature of the cationic substance may also influence the rate of the photochemical decomposition, but sufficient data are not available to enlarge upon this point.…”
Section: Effect Of Pretreatment With Different Cationic Substancesmentioning
confidence: 98%
See 4 more Smart Citations
“…It is seen that the stability of the silk to light increases WIth increase in pH of the solutions used for treatment of the silk. This is to be expected, since as shown by the titration curve of silk [6], the binding of cations also increases with increasing pH. In addition to pH, the chemical nature of the cationic substance may also influence the rate of the photochemical decomposition, but sufficient data are not available to enlarge upon this point.…”
Section: Effect Of Pretreatment With Different Cationic Substancesmentioning
confidence: 98%
“…• 'rbe cboice of tbis pH was based on tbe titration studies of GJeysteen snd Harris [6] in which it was sbown that removal of cations from silk becomes appreciable below about pH 3. and is not caused by the presence of free acid in the exposed samples. It was found that none of the silk samples kept in the dark exhibited any deterioration, showing that the deterioration of the irradiated silk ti:…”
Section: Effect Of Removal Of Cations On the Rate Of Deteriorationmentioning
confidence: 99%
See 3 more Smart Citations